Effectiveness executive function training program using augmented reality on Communication skills in children with high-functioning autism spectrum disorder - Shirin Mojaver; Aliakbar Arjmandnia; Mohsen Shokoohi yekta; Bagher Ghobari bonab; Fatemeh Jafarkhani (روانشناسی و روانپزشکی شناخت)
Introduction: Children with autism spectrum disorder have deficiencies in verbal or nonverbal communication skills. It seems that executive functions training using augmented reality can improve the communication skills of children with autism spectrum disorder. Aim: The aim of the present study was to investigate the effectiveness of an executive functions training program using augmented reality on communication skills in children with high-functioning autism spectrum disorder. Method: The present study was a quasi-experimental study with a pre-test-post-test design and a control group with a one-month follow-up period. The statistical population of the study included all children with high-functioning autism spectrum disorder in Tehran in 2023-2024, from which 30 people were selected through purposive sampling and randomly assigned to two experimental (15 people) and control (15 people) groups. Participants answered the Gilliam Autism Diagnostic Scale - Second Edition (1995) for pre-test and post-test. After 21 45-minute sessions of executive functions training using augmented reality for children in the experimental group, the statistical method of analysis of variance with repeated measures and SPSS24 software were used to analyze the data. Results:The findings showed that the executive functions training program using augmented reality had a significant effect on the control group in the two stages of post-test and follow-up (p<0.001). Conclusion: Executive functions training using augmented reality is effective on the communication skills of children with autism spectrum disorder and this training is recommended for children with autism spectrum disorder.